Influence of cathode and anode processes on tribocorrosion of aluminium alloy AA2024 in acid rain - M. Khoma; V. Vynar; Сh.Vasyliv; A. Dykha; Yu. Kovalchyk (Проблеми трибології, 2021)
The nature of cathodic processes during the frictional interaction of aluminum alloy with ball corundum in the conditions of reciprocating motion has been studied. Under conditions of anodic polarization under conditions of friction, corrosion processes are activated and their speed during friction increases many times. The potential on the surface of the alloy under acid rain shifts sharply in the negative direction. Changes in the tribopotential and coefficient of friction are characterized by a gradual shift in values at the initial stage of research. The oxide film is formed on the metal surface in neutral and acidic environments. The service life of the film is increased due to electrochemical protection during cathodic polarization at the electrode potential of pure alloy without oxide film. It is proved that polarization changes the life of the film in the initial stages and the loss of material and the coefficient of friction during the entire test period. It is established that the nature of surface fracture also changes as a result of application of the polarization potential during friction. The largest surface damage is observed during anodic polarization